Analisis Manajemen Kelas pada Pembelajaran PAI dalam Meningkatkan Partisipasi Belajar Siswa - Nova Riska Nurafianti; Acep Rahmat; Ahmad Jamal rohman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to determine classroom management in the Islamic Religious Education (PAI) learning process to increase student engagement at Persada Bayongbong Junior High School. This study used a qualitative approach with descriptive methods. The research subjects included Islamic Religious Education (PAI) teachers, student affairs teachers, and eighth-grade students. Data were collected through observation, interviews, and documentation. Data analysis was conducted through three steps: data reduction, data presentation, and conclusion drawing.The findings of this study indicate that classroom management was implemented through planning, organizing, implementing, and evaluating. In the planning stage, teachers prepared learning materials, established classroom rules, and designed a variety of learning methods. In the organizing stage, teachers effectively managed learning activities, students, and facilities and infrastructure. In the implementation stage, discussion and question-and-answer methods were more effective in increasing student participation than lecture methods. In the evaluation stage, learning outcomes in the cognitive aspect were satisfactory, but the affective and psychomotor aspects needed improvement. The level of student participation was moderate, with most students being non-verbal. Some students showed low levels of engagement, necessitating the use of more creative and interactive learning methods.